ANALISIS KEBIJAKAN INSTRUKSI BUPATI KUNINGAN NOMOR 7 TAHUN 2020 TENTANG PELAKSANAAN PROGRAM PENGANTIN PEDULI LINGKUNGAN - Banafsaj Shafa Sholihat, - (2023)
This research is motivated by environmental problems which are then formed policies to overcome them. The environmental care bridal program policy in Kuningan Regency was formed with the aim of overcoming environmental problems by carrying out a green movement through community empowerment. The target of implementing the environmental care bridal program is the bride and groom in the form of handing over plant seeds. The selection of policy subject targets is based on the number of marriage events in Kuningan District each year. Therefore, the environmental care bridal program carried out by the people of Kuningan Regency and the Regional Government of Kuningan Regency is aimed at accelerating the rehabilitation of critical lands and encouraging public awareness to participate in managing natural resources so that they provide maximum benefits for the welfare of the community. This study aims to find out and describe how the environmental care bridal program is implemented. The research design used in this research is a qualitative approach with descriptive methods, while the data collection technique is done by interviews, observations, documentation studies, and field notes. Furthermore, the data that has been collected is analyzed by means of data reduction, data presentation, and drawing conclusions. The results of the research that has been done can analyze and describe a number of things (1) The environmental care bridal program is carried out in the form of handing over 2 plant seeds to the prospective bride and groom. Not only that, in policy implementation, what is also important is related to seed storage and seed distribution. In carrying out the policy, there are institutions in charge, namely management institutions and supervisory institutions. In the implementation of the environmental care bride program policy, it can be said that it is going well even though it is still not in accordance with the policies made and is still experiencing several obstacles. (2) the results of the implementation of the environmental care bridal program can be seen from the policy output in the form of seeds that are collected which ultimately have an impact on changes in environmental quality, and the impact of the policy can be seen from changes in people's sense of concern for their environment. (3) the successful implementation of the policy which in fact is still not as expected is a form of the occurrence of obstacles in the implementation of the policy, these obstacles can be seen from several indicators, namely communication, resources and dispositions.